Health financing for universal coverage and health system performance: concepts and implications for policy - Joseph Kutzin (The World Health Organization, 2013)
Abstract Unless the concept is clearly understood, "universal coverage" (or universal health coverage, UHC) can be used to justify practically any health financing reform or scheme. This paper unpacks the definition of health financing for universal coverage as used in the World Health Organization's World health report 2010 to show how UHC embodies specific health system goals and intermediate objectives and, broadly, how health financing reforms can influence these. All countries seek to improve equity in the use of health services, service quality and financial protection for their populations. Hence, the pursuit of UHC is relevant to every country. Health financing policy is an integral part of efforts to move towards UHC, but for health financing policy to be aligned with the pursuit of UHC, health system reforms need to be aimed explicitly at improving coverage and the intermediate objectives linked to it, namely, efficiency, equity in health resource distribution and transparency and accountability. The unit of analysis for goals and objectives must be the population and health system as a whole. What matters is not how a particular financing scheme affects its individual members, but rather, how it influences progress towards UHC at the population level. Concern only with specific schemes is incompatible with a universal coverage approach and may even undermine UHC, particularly in terms of equity. Conversely, if a scheme is fully oriented towards system-level goals and objectives, it can further progress towards UHC. Policy and policy analysis need to shift from the scheme to the system level.